Tindak Tutur Ilokusi Pidato Probowo Subianto Dalam Acara Penutupan Kongres VI PAN 2024 - Cici Ediana; Zuraida Khairani; Eva Fitrianti (Kilau Publishing, 2025)
Based on the problem that many Indonesians still misunderstand or inaccurately interpret the meaning of Prabowo Subianto’s speech because the audience comes from different backgrounds of experience, education, culture, and emotion, they may fail to properly understand the meaning of the illocutionary speech acts contained in Prabowo Subianto’s speech. Therefore, this study aims to describe the forms and functions of illocutionary speech acts in Prabowo Subianto’s speech at the closing ceremony of the 6th PAN Congress in 2024. This research is a qualitative study using a descriptive approach. The main instrument of this research is the researcher, while the supporting instruments are stationery and data tables. The data source of this study is Prabowo Subianto’s speech at the closing ceremony of the 6th PAN Congress in 2024. The data collection techniques used are observation and documentation. The data were analyzed through data reduction, data presentation, and drawing conclusions. To ensure data validity, theoretical triangulation was used. The results of this study show that there are 103 data related to the forms of illocutionary speech acts in Prabowo Subianto’s speech at the closing ceremony of the 6th PAN Congress in 2024, along with their functions. The forms of illocutionary speech acts include expressive speech acts with 41 data, directive speech acts with 29 data, assertive speech acts with 19 data, commissive speech acts with 9 data, and declarative speech acts with 4 data. The functions of illocutionary speech acts consist of competitive functions with 16 data, convivial functions with 38 data, collaborative functions with 33 data, and conflictive functions with 16 data. These four functions form the foundation of meaning in each utterance delivered by the speaker through his speech.